2020
DOI: 10.2147/opth.s233816
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effect of Funding Source on “Spin” in Studies of Ocriplasmin Therapy for Vitreomacular Traction and Macular Hole</p>

Abstract: Purpose: To examine the relationship between industry funding and "spin" in randomized controlled trials (RCTs) and meta-analyses investigating use of ocriplasmin for patients with vitreomacular traction (VMT) and macular hole (MH). Methods: In this study, we examined all PubMed and Ovid MEDLINE RCTs and metaanalyses published in journals with impact factor ≥2 investigating effectiveness of ocriplasmin use for VMT and MH. The main outcome measure was correspondence between the studies' main statistical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The significant associations found between the Scopus CiteScore, Clarivate Impact Factor, external funding, and preregistration with PROSPERO were surprising given the fact that previous findings of other spin studies have found no statistically significant associations between these variables and spin types. 20 , 24 , 25 , 26 Failure to adhere to AMSTAR type 9 (“Did the review authors use a satisfactory technique for assessing the RoB [risk of bias] in individual studies that were included in the review?”) was significantly associated with both a lower Scopus CiteScore ( P = .015) and Clarivate Impact Factor ( P = .00059). One explanation is that the studies that did not report using a validated risk of bias tool were only able to be published in lower-quality journals, as lack of accurate assessment of bias can result in distortion of results reporting.…”
Section: Discussionmentioning
confidence: 99%
“…The significant associations found between the Scopus CiteScore, Clarivate Impact Factor, external funding, and preregistration with PROSPERO were surprising given the fact that previous findings of other spin studies have found no statistically significant associations between these variables and spin types. 20 , 24 , 25 , 26 Failure to adhere to AMSTAR type 9 (“Did the review authors use a satisfactory technique for assessing the RoB [risk of bias] in individual studies that were included in the review?”) was significantly associated with both a lower Scopus CiteScore ( P = .015) and Clarivate Impact Factor ( P = .00059). One explanation is that the studies that did not report using a validated risk of bias tool were only able to be published in lower-quality journals, as lack of accurate assessment of bias can result in distortion of results reporting.…”
Section: Discussionmentioning
confidence: 99%